HUMAN SUBJECTIVITY: A Philosophical Investigation after Wittgenstein - Nandhikkara, Jose (Journal of Dharma, 2008)
Wittgenstein often labelled his later philosophical investigations as "grammatical investigations" (PR 52, PG 71, PI 90, 150). According to him, "A main source of our failure to understand is that we do not command a clear view of the use of our words. - Our grammar is lacking in this sort of perspicuity" (PI 122). This is true about the words that we use for human beings. Besides the proper names and personal pronouns, we use words like ego, self, soul, mind, spirit, reason, will, etc., to define, describe, or refer to human beings. By arranging Wittgenstein’s relevant remarks I would like to render a synoptic view of ‘human being’ showing various connexions as well as differences of our uses of words that refer to human subjectivity. "Language," Wittgenstein wrote, "is a labyrinth of paths. You approach from one side and know your way about; you approach the same place from another side and no longer know your way about" (PI 203). The object of philosophy is to provide us with an Übersicht of our use of words so that we know our way about (PI 123). Besides labyrinth, Wittgenstein used the metaphors of fly-bottle (PI 309) and jigsaw puzzle (BB 46) to draw our attention to certain pitfalls and confusions in many philosophical questions. We are driven to certain ways of thinking which are far from the actual use of words. "The thing to do in such cases," according to Wittgenstein, "is always to look how the words in question are actually used in our language" (BB 56). For, "only in the stream of thought and life do words have meaning" (Z 173). Our real need in life is the norm of our philosophical investigations.